Using theory to understand how policy change happens: Insights from agricultural research for development - Douthwaite, Boru; Proietti, Claudio; Polar, Vivian; Thiele, Graham (Oxford University Press, 2023)
Influencing policy is an important scaling mechanism. However, if a program is to plausibly claim that it has or can influence policy, it needs to explain how. This is not straightforward because of the complex nature of policy change. Scholars suggest the use of theory to help answer the ‘how’ question. In this article, we show how, in practice, a middle-range policy change theory—Kingdon’s Policy Window theory—helped us model the workings of four outcome trajectories that produced agricultural policy outcomes in four cases. By providing a common framework, the middle-range theory helped accumulate learning from one evaluation to the next, generating specific and generalizable insights in the process. Accumulation learning in this way can help organizations become more convincing in the proposals they write to donors, more accountable and better able to identify and deliver on their goals.